LEGAL ISSUES IN E-WALLET PRACTICES (UUM Journal of Legal Studies, 2021)
E-Wallet has been applied in Muslim and non-Muslim jurisdictions in many parts of the world including Malaysia, China, India, and Korea. The application is widely used and has raised questions with regard to legal and shariah issues. This paper aims to analyse specifically, legal issues affecting e-wallet practices. This paper adopted a qualitative research approach. The data collected include document reviews, ethnographical interviews and observations. This study found several legal issues related to e-wallet inter alia, an unclear position on the liability of board directors of e-wallet operators, breach of mandate and exclusion of liability of e-wallet operators. As e-wallet is important as an enabler to increase financial inclusion, it is important to address the legal issues on e-wallet to enhance good governance and best practices of e-wallet in Malaysia. The findings from this paper can be used as a basis for policymakers including scholars in the formulation of guidelines on legal and shariah compliance of e-wallets.